ANOVA-Based Analysis of the Effect of Healthqual Dimensions on Customer Satisfaction in Healthcare Facility XYZ’s Market Segments - Haninda Pundhiningtyas; Whidya Utami; Teofilus Teofilus (Publikasi Indonesia, 2025)
In the face of growing competition from modern healthcare facilities offering advanced diagnostic technologies, efficient processes, and competitive pricing, Healthcare Facilty XYZ Surabaya must maintain and enhance service quality to meet customer expectations. Customer satisfaction remains a crucial factor for long-term success by ensuring loyalty and positive recommendations. This study aims to analyze the influence of the five HEALTHQUAL dimensions (Tangibility, Efficiency, Safety, Empathy, and Improvement of Service) on customer satisfaction in Healthcare Facility XYZ. The underlying phenomenon lies in the variation in patient perceptions, where some indicators—such as cleanliness, timeliness of results, and a sense of safety—are perceived as basic standards, while factors like staff competence, simple procedures, friendliness, waiting room comfort, and digital access to results serve as more decisive indicators of satisfaction. A quantitative approach was employed, involving validity and reliability testing, as well as analysis of variance (ANOVA) to identify dominant indicators and differences across customer segments. The findings reveal that waiting room comfort, uncomplicated procedures, medical staff competence, friendliness, and electronic access to results significantly affect customer satisfaction, while parking availability, timeliness of results, perceived safety, attention to comfort, and feedback requests are not significant. ANOVA results further highlight Safety and Improvement of Service as the main dimensions contributing to satisfaction, although their effects vary across segments. These results suggest a need for adaptive health service strategies that prioritize patient safety and service innovation to achieve optimal satisfaction.